Population Estimate for the Bluenose-East Caribou Herd Using Post-calving Photography - Patterson, Brent R.; Olsen, Benjamin T.; Joly, Damien O. (ARCTIC, 2004)
Genetic and spatial analyses suggest that what was previously described as the Bluenose herd of barren-ground caribou (Rangifer tarandus groenlandicus) comprises three separate populations. Of these, the Bluenose-East caribou herd (BECH) has received little coverage in past surveys. Existing estimates of abundance suggested that current harvest rates of Bluenose-East caribou (~5000 animals/year) might be excessive. We used post-calving photography in June-July 2000 to estimate the size of the BECH. A maximum of 33 radio-collared caribou were available for location in June 2000. We located 30 of these caribou and photographed distinct groups containing 23 collared individuals. Excluding caribou assumed to belong to the neighboring Bluenose-West herd, we photographed a minimum of 84 412 adult and 4193 calf caribou. Using a simple mark-recapture model to account for caribou associated with collared individuals not photographed, we calculated an estimate of 104 000 ± 22 100 (95% CI 84 412 - 126 100) non-calf caribou. A recently published stochastic model produced a considerably higher and more variable estimate of 208 700 (95% CI 112 600 - 474 700). In March 2001, we deployed seven more radio collars in anticipation of repeating the census in 2001, but poor weather conditions precluded the formation of large aggregations. Present densities of Bluenose-East caribou seem high, and we recommend regular monitoring of body condition to assess the potential for a forage-induced population crash. Des analyses génétiques et spatiales suggèrent que ce que l'on a décrit précédemment comme le troupeau de caribous des toundras Bluenose (Rangifer tarandus groenlandicus) est en fait composé de trois populations distinctes. De ces trois hardes, le troupeau de caribous Bluenose de l'Est (TCBE) n'a pas reçu beaucoup d'attention au cours des relevés antérieurs. Les estimations d'abondance qui existent ont suggéré que le taux de prélèvement actuel de ce caribou (~ 5000 animaux/an) pourrait être excessif. On a eu recours à des ...